Link Budget Site Planning in Kuranji Region Andalas University - Mount Sarik - Marisa Cania; Dikky Chandra; Yustini Yustini (Politeknik Negeri Padang, 2024)
Link budget is a way to calculate all parameters in signal transmission, ranging from gain and loss from the transmitter to the receiver via transmission media. This design is motivated by planning at PT. Alita Praya Mitra for site development in Kuranji region – University Andalas (UNAND) – Gunung Sarik with the reason to provide improved operator services, especially XL operator. In this final project to design using Pathloss 4.0 software as a tool that can facilitate a planner in calculating link budget. In this design the parameters used are propagation distance between sites, Effective Isotropic Received Power (EIRP), Free Space Loss (FSL), Isotropic Received Level (IRL), Received Signal Level (RSL) and Fade Margin (FM). On the calculation of the microwave transmission line of the kuranji area - University Andalas with a propagation distance of 1.17 km, University Andalas - Gunung Sarik with a propagation distance of 1.01 km, Gunung Sarik – Kuranji with a propagation distance of 1.19 km.